Anesthetic Management of Cavernous Sinus Meningioma with Pre-existing Cranial Nerve Deficits: A Case Report - Rahmadhona, Sri; Lubis , Bastian (Journal of Society Medicine, 2026)
Cavernous sinus meningioma poses significant neuroanesthetic challenges due to its skull base location, close proximity to critical neurovascular structures, and frequent association with pre-existing cranial nerve dysfunction. Optimal perioperative anesthetic management is essential for preserving cerebral perfusion pressure, maintaining optimal intracranial dynamics, and preventing secondary brain injury during complex skull base surgery. We report the perioperative anesthetic management of a 52-year-old woman with a right cavernous sinus meningioma who presented with a five-month history of progressive headache and multiple cranial nerve deficits, including ptosis, facial hypoesthesia, and deviation of the mouth and tongue, without limb motor weakness. The patient had long-standing poorly controlled hypertension and was classified as American Society of Anesthesiologists physical status III. Preoperative assessment demonstrated stable cardiopulmonary function, anisocoria, and preserved consciousness. Magnetic resonance imaging revealed a right cavernous sinus tumor measuring 2.4 × 1.7 × 1.9 cm. The patient underwent elective craniotomy and tumor removal under general anesthesia with endotracheal intubation. A comprehensive neuroprotective anesthetic strategy was implemented, including head-up positioning, controlled ventilation to maintain normocapnia, strict hemodynamic control to preserve cerebral perfusion pressure, and goal-directed fluid and blood management. The surgical procedure lasted six hours with an estimated blood loss of 1600 mL, managed with crystalloid, colloid, and blood component therapy. Postoperatively, the patient was managed in the intensive care unit with mechanical ventilation, adequate analgesia and sedation, osmotherapy, anticonvulsant prophylaxis, and close neurological monitoring. Despite transient metabolic acidosis, the patient remained hemodynamically stable, with preserved oxygenation and neurological improvement.